A forma????o de alunos(as) num curso superior de gastronomia: aprendizagem, cultura e cidadania - Menezes, Maria Cristina Pinto de (2005)
This research investigated the student development process of a Gastronomy undergraduated course in S??o Paulo. It was analized how this development process is carried out in these students, while students or citizens and how their identity is modeled in accordance to the market place they want to be in. To reach our goals, we analysed the scenario in which the Gastronomy and Hotel Administration undergraduated course, like technological branch, are inserted. To do so, we researched its related history and legislation, its origin as practical knowledge that recently became an area of interest for the academical area. The thesis focus is the student body itself. We analyzed his/her profile, asking a sample of students about his/her opinion on education and life conditions . We also made use of some students self-written life history. The theme analisis guided us to better know the essential elements for the student development process. We searched to understand this process through some basic concepts, such as citizenship, culture, identity, emancipation, social participation, non-formal education and assertiveness. This study concluded that the majority of researched students came from medium levels of society and have idealist thougths about the market place. Their professional choices came from, for most of them, their memories and life history. Happiness is a fundamental objective to their professional success. Family is highly valued. School is seen as part of their working hours and they approved the education they receive. Their professional identity is modelled by incorporating the demands of a even more competitive environment: good physical appearance and behaviour, experience in renowned restaurants and hotels and living abroad. However, the old dream of entrepreneurship is still strong.